In situ synthesis and electronic transport of the carbon-coated Ag@C/MWCNT nanocomposite. Issue 14 (15th February 2018) - Wang, Dongxing; Li, Da; Muhammad, Javid; Zhou, Yuanliang; Wang, Ziming; Lu, Sansan; Dong, Xinglong; Zhang, Zhidong
Abstract : An electric transition from ln ρ ( T ) ∼ T −1/4 to ln ρ ( T ) ∼ T −1/2 hopping conduction happened at 5.4 K in situ synthesis of Ag@C/MWCNTs nanocomposite. Abstract : A nanocomposite of Ag@C nanocapsules dispersed in a multi-walled carbon nanotube (MWCNT) matrix was fabricated in situ by a facile arc-discharge plasma approach, using bulk Ag as the raw target and methane gas as the carbon source. It was found that the Ag@C nanocapsules were ∼10 nm in mean diameter, and the MWCNTs had 17–32 graphite layers in the wall with a thickness of 7–10 nm, while a small quantity of spherical carbon cages (giant fullerenes) were also involved with approximately 20–30 layers of the graphite shell. Typical dielectric behavior was dominant in the electronic transport of Ag@C/MWCNT nanocomposites; however, this was greatly modified by metallic Ag cores with respect to pure MWCNTs. A temperature-dependent resistance and I – V relationship provided evidence of a transition from Mott–David variable range hopping [ln ρ ( T ) ∼ T −1/4 ] to Shklovskii–Efros variable range hopping [ln ρ ( T ) ∼ T −1/2 ] at 5.4 K. A Coulomb gap, Δ C ≈ 0.05 meV, was obtained for the Ag@C/MWCNT nanocomposite system.